2013
DOI: 10.1075/wll.16.1.04tib
|View full text |Cite
|
Sign up to set email alerts
|

Emergent writing of young children in the United Arab Emirates

Abstract: We report results of writing samples of six Emirati children aged four to four and a half years collected at monthly intervals over an eight month period (the kindergarten academic year). Three teachers and six parents were interviewed to triangulate the data that were collected in the classrooms. The grounded theory method was used to code and categorize the data, which were then compared with the literature on emergent writing. Findings of this longitudinal study revealed that few opportunities are provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Early vocabulary and letter naming skills of Arabic-speaking children in kindergarten were correlated with home literacy activities, with joint writing being a significant contributor to first grade reading achievement (Aram, Korat, & Hassunah-Arafat, 2013). In the absence of Arabic-language books, parents with a range of literacy skills can engage in creating their own literacy materials for a shared writing experience with tasks as simple as drawing, writing approximations, making lists, and writing names (Tibi, Joshi, & McLeod, 2013). Promoting shared reading and writing among Syrian parents and their children can help to bridge the gap between home and school practices.…”
Section: Suggestions For Syrian Refugee Families On L1 Language and Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Early vocabulary and letter naming skills of Arabic-speaking children in kindergarten were correlated with home literacy activities, with joint writing being a significant contributor to first grade reading achievement (Aram, Korat, & Hassunah-Arafat, 2013). In the absence of Arabic-language books, parents with a range of literacy skills can engage in creating their own literacy materials for a shared writing experience with tasks as simple as drawing, writing approximations, making lists, and writing names (Tibi, Joshi, & McLeod, 2013). Promoting shared reading and writing among Syrian parents and their children can help to bridge the gap between home and school practices.…”
Section: Suggestions For Syrian Refugee Families On L1 Language and Lmentioning
confidence: 99%
“…Korat et al (2012) cited several other examples of parent mediation strategies, such as relating to illustrations, orally telling a story, connecting story content to child experiences, and discussing written text, all of which can be used alongside paraphrasing to promote children's understanding and to hone oral language skills. Educators and SLPs should exercise sensitivity to parents' decisions regarding their roles as Arabic-language teachers of their children, especially in the practice of standard Arabic (Tibi et al, 2013), and encourage parents to engage their children in oral language or literacy activities that will be sustainable and naturally occurring in their homes without imposing prevailing ideas about education onto resettled families.…”
Section: Suggestions For Syrian Refugee Families On L1 Language and Lmentioning
confidence: 99%
“…However, parents in some studies appear to view their responsibilities as relatively small in their children’s early formal learning. For example, in a study involving six parents in the United Arab Emirates, the parents showed little awareness of the importance of parent-child interactions and stimulating early home environments to support their children’s emergent writing skills ( Tibi et al, 2013 ). The Kazakhstani mother in a case study by Amantay (2017) also expressed the idea that literacy was “something special” (p. 31) and believed that parents had little to do at home to promote children’s literacy development.…”
Section: What Learning-related Beliefs and Attitudes Do Parents In Asmentioning
confidence: 99%
“…According to the Ministry of Education's policy, kindergarten teachers should use MSA in the classroom. However, a longitudinal observational study of three kindergarten classrooms by Tibi, Joshi, and McLeod (2013) found that only one of the teachers actually used standard forms, although all of them recognized that they were required to do so.…”
Section: Teacher Qualitymentioning
confidence: 99%
“…There are fewer published studies of early biliteracy development in languages where alphabets and directionality differ, such as Chinese and English (Yaden and Tsai 2012) (Zhang and Guo 2017). There are even fewer studies of Arabic-English biliteracy acquisition where linguistic distance also pertains, and these include studies by Saiegh-Haddad and Geva (2007) and in the UAE by Tibi, Joshi, and McLeod (2013).…”
Section: Optimal Conditions For Emergent Biliteracy Educationmentioning
confidence: 99%